2019
DOI: 10.3390/genes10010053
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Genetic Epidemiology: A Latin American Perspective

Abstract: There are an estimated 10 million new cases of tuberculosis worldwide annually, with 282,000 new or relapsed cases each year reported from the Americas. With improvements in genome sequencing technology, it is now possible to study the genetic diversity of tuberculosis with much greater resolution. Although tuberculosis bacteria do not engage in horizontal gene transfer, the genome is far more variable than previously thought. The study of genome-wide variation in tuberculosis has improved our understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 126 publications
5
35
0
1
Order By: Relevance
“…As a second aim we described for the first time, the molecular epidemiology of tuberculosis in Guatemala. The most common spoligotypes families found in this study, LAM, T and Haarlem are similar to the ones obtained in South America, although their proportion varied according to the country as recently reviewed [32, 33]. Nevertheless, the X family accounted for less than 7% in the majority of these studies and we found a prevalence of 13%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As a second aim we described for the first time, the molecular epidemiology of tuberculosis in Guatemala. The most common spoligotypes families found in this study, LAM, T and Haarlem are similar to the ones obtained in South America, although their proportion varied according to the country as recently reviewed [32, 33]. Nevertheless, the X family accounted for less than 7% in the majority of these studies and we found a prevalence of 13%.…”
Section: Discussionsupporting
confidence: 89%
“…Lineage 4 is one of the seven lineages in which are categorized M. tuberculosis complex strains and is the one with the largest distribution in the world [35, 36]. Its introduction in the Americas is considered to be owed to the European colonization of the continent after the 1500s [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the transmission of MTB depends on its ability to damage lung tissues to a large extent. 25 Consequently, DR-MTB with substantial lung tissue damage is likely to cause the extensive spread of TB lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the lineages, the Brazilian profile observed in this demonstrate the higher frequency of Lineage 4, mainly LAM genotype and the higher frequency of Lineage 1 in Pará State. 130 , 131 , 132 , 133 The presence of M. tuberculosis var. bovis among human strains was not reported so far, and M. tuberculosis var.…”
Section: Discussionmentioning
confidence: 99%